"I Am Most Grateful." Using Gratitude to Improve the Sense of Relatedness and Motivation for Online Volunteerism. Issue 14 (26th August 2020) - Naqshbandi, Khushnood Z.; Liu, Chunfeng; Taylor, Silas; Lim, Renee; Ahmadpour, Naseem; Calvo, Rafael
ABSTRACT: Volunteering benefits those who receive and those who provide help. Yet barriers can inhibit engagement with and motivation for volunteering activities. Online environments on one hand help to lower some of these barriers, but on the other hand they can introduce new obstacles specially when the medium transforms the social interactions important to volunteers. We study the motivational drivers of online volunteering, and how those are affected by design. Specifically, we focus on relatedness as a source of motivation. We describe two studies with volunteers that help medical students to learn and improve their communication skills through mock interviews in an educational program. The volunteers can participate in the program face-to-face or through an online platform. The first study consisted of a survey (n = 66 volunteers), two workshops and one interview (n = 12 volunteers) in which we explored volunteer demographics, motivations, psychological needs, and experiences. Findings suggested relatedness can be an important indicator of volunteer motivations. In the second study, we added a feature to the online platform to display personal gratitude messages from student beneficiaries to the volunteers in order to improve the experience of relatedness between them. In total, n = 30 volunteers completed 196 sessions. We used survey and system data to assess the impact of gratitude on perceived relatedness, motivation, and behavior (immediate, booked, and completed appointments). Results showed that the expression of gratitude by the beneficiary significantly affected the volunteer's experience of relatedness which then correlated with immediate appointments booking behavior by each volunteer. The implications for design of online volunteering systems are discussed.